2012
DOI: 10.1016/j.bpj.2012.08.030
|View full text |Cite
|
Sign up to set email alerts
|

TATA Binding Proteins Can Recognize Nontraditional DNA Sequences

Abstract: We demonstrate an accurate, quantitative, and label-free optical technology for high-throughput studies of receptor-ligand interactions, and apply it to TATA binding protein (TBP) interactions with oligonucleotides. We present a simple method to prepare single-stranded and double-stranded DNA microarrays with comparable surface density, ensuring an accurate comparison of TBP activity with both types of DNA. In particular, we find that TBP binds tightly to single-stranded DNA, especially to stretches of polythy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…A deeper understanding of these interactions involving TFs can shed light on the eukaryotic transcription initiation processes, hence the resultant gene expression regulations. With this goal in mind, IRIS has been used to study those interactions in [ 19 ]. Specifically, the study explores TATA binding protein (TBP), a key TF that takes part in the initiation of eukaryotic transcription.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…A deeper understanding of these interactions involving TFs can shed light on the eukaryotic transcription initiation processes, hence the resultant gene expression regulations. With this goal in mind, IRIS has been used to study those interactions in [ 19 ]. Specifically, the study explores TATA binding protein (TBP), a key TF that takes part in the initiation of eukaryotic transcription.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…But as per our knowledge, this feature has not been detected in the human genome at this scale. ( 38 ) showed that TATA-binding proteins can bind poly- tracts and that a small fraction of human core promoters contain a TATA-box followed by a -rich region upstream of the TSS.…”
Section: Resultsmentioning
confidence: 99%
“…To define the gonococcal Fur regulon more efficiently, we developed a microarray-based, label-free quantitative method utilizing IRIS to screen sequence-specific interactions of Fur to dsDNA in vitro [5], [34]. Combining this approach with bioinformatical analysis of the gonococcal genome and transcriptional analysis of N. gonorrhoeae wild type, fur mutant and fur complemented strains, we identified new Fur regulated genes.…”
Section: Introductionmentioning
confidence: 99%
“…IRIS can be broadly applied to characterize many types of biomolecular interactions, such as DNA-DNA hybridization, protein-protein binding, and protein-DNA interaction in a quantitative format [1] , [2] , [3] , [4] . Specifically, this technique has previously demonstrated utility for probing transcription factor interactions with arrayed oligonucleotides [5] . Bacterial transcription factors control tight regulation of gene expression in response to host specific environmental niches in a number of human pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation